THE USE OF MODERN ANTIBIOTICS IN NURSING PRACTICE: IMPLICATIONS FOR PATIENT CARE AND INFECTION MANAGEMENT (Modern education and development, 2024)
Antibiotics are crucial in the treatment of bacterial infections, and modern antibiotics have revolutionized patient care by offering effective solutions for a range of infections. However, the misuse and overuse of antibiotics have led to the growing issue of antibiotic resistance, which poses a significant threat to public health. This article examines the role of nurses in the use of modern antibiotics, highlighting their responsibilities in administering medications, educating patients, and preventing the development of resistance. Emphasis is placed on the importance of evidence-based practices, appropriate antibiotic selection, and patient safety in nursing care.